Experiences of Discrimination Among Women and Gender Diverse Veterans Using Veterans Health Administration Health Care - Jodie G. Katon; Samantha K. Benson; Vyshnika Sriskantharajah; Lisa S. Callegari; Karissa Fenwick; Kristen E. Gray; P. Adam Kelly; Ashley C. Mog (Health Equity)
Introduction: Women Veterans are diverse in terms of racial, ethnic, and gender identities and sexual orientation and may experience a variety of forms of discrimination and stigma in health care settings. Our objective was to understand discrimination experienced by women Veterans in the context of Veterans Health Administration (VA) care. Methods: We analyzed data from a series of semistructured telephone interviews with Veterans identified as females in the VA medical record who received VA health care in the past 12 months, purposively sampled by race/ethnicity and age (N = 28). The interview guide elicited experiences with VA health care, including discrimination. Interviews were audio-recorded, transcribed, and analyzed using inductive and deductive content analysis. Results: We identified themes regarding structural discrimination, interpersonal discrimination, and strategies employed in response to discrimination. Veterans described structural discrimination, including challenges with spaces not designed to accommodate disabilities or safety needs and care not sensitive to their gender, trauma histories, or sexual orientation. Interpersonal discrimination included harassment from other Veterans and biased treatment from VA providers and staff based on gender, appearance, and sexual orientation. Gender-based discrimination compounded across additional axes of marginalization including body size and stigma regarding mental illness. Experiences of discrimination undermined Veterans’ sense of belonging and trust in VA and created barriers to accessing care. Veterans engaged in various strategies to protect themselves from discrimination and get needed care. Discussion: Quality improvement efforts that address the experience of women Veterans using VA health care must consider multiple forms and sources of discrimination and the intersection of gender-based discrimination with other forms of marginalization.